Supercapacitor based on activated carbon and hybrid solid polymer electrolyte - Hashim, MA; Khiar, ASA (Maney Publishing, 2024)
The main objective of the present work is to develop a high conducting hybrid solid polymer electrolyte (HSPE) using polyvinyl alcohol as the host polymer and H(3)PO(4) as the ionic dopant. Owing to its porous nature, the introduction of a Whatman filter paper helps to increase the electrical conductivity by acting as a support to the electrolyte system. This allows more H(3)PO(4) acid to be loaded into the system and thus helps to improve the mechanical strength of the electrolytes. The highest conducting HSPE was obtained at 1.04 x 10(-4) S cm(-1) for samples containing 70% loading of acid (P30H70-C). Such conductivity is sufficient for application in an electrical double layer capacitor (EDLC). The EDLC was fabricated using the hybrid electrolyte with its activated carbon electrodes soaked in H(3)PO(4). A specific capacitance of 34 F g(-1) with internal resistance of as low as 1 Omega cm(-2) was obtained when the cell was charged-discharged at 10 mA. The working voltage for this EDLC is 1 V with efficiency ranging between 85 and 97%.